Perspektif Hukum Ekonomi Syariah Tentang Perlindungan Konsumen pada Transaksi Jual Beli di Live Streaming Tiktok Shop - Sulthonuddin, Bung Hijaj; Muttaqin, Tegar Abdul Fatah (Jurnal Hukum Ekonomi Syariah, 2024)
In its development in the digital era, buying and selling transactions have undergone a significant transformation. The presence of e-commerce services such as Shopee, Lazada, Tokopedia and others has become a new trend in buying and selling transactions. Not only e-commerce platforms that are specifically intended for buying and selling activities, even social media platforms such as Facebook with its marketplace, TikTok with its Live streaming TikTok Shop are intensively working on the shopping feature in accommodating this online shopping trend. This study aims to find out how the mechanism of buying and selling transactions in Tiktok shop live streaming, what is the perspective of Sharia Economic Law on buying and selling transactions in Tiktok shop live streaming and to find out how to implement consumer protection from the perspective of Sharia Economic Law on buying and selling transactions in TikTok Shop Live Streaming. This research is a qualitative research using the libarary research method. The results of this study show that through the approach of fulfilling consumer rights, the researcher concludes that consumer protection when taken from the perspective of consumer rights in buying and selling transactions on Tiktok shop live streaming has been fulfilled and in accordance with the perspective of sharia economic law.  Keywords: Consumer Protection; Sharia Economic Law; Tiktok Shop